Paralisia cerebral e institucionalização: efeitos subjetivos e clínica de linguagem - Dudas, Tatiana Lanzarotto (2009)
There are, in the Speech Therapy and Pathology areas, some but not many researches who have approached questions related to clinical procedures involving persons with the nosological classification labeled Cerebral Palsy. It is worth mentioning that all of them are oriented by organicist and/or socio-cognitivist viewpoints. The absence of a spoken language , very common in the most serious cases of such a disease, may be the relevant factor in the scenario. Indeed, researchers and professionals may conclude that when there is no speech, there is no speaker, that is, that the person at stake is out of language . However, perception and cognitive capacities and skills are assumed. In other words, they are assumed to be independent of language. According to this kind of reasoning, language and its effects on the subject are ignored. Exceptional cases in the area are those that are submitted a consistent language theory which is articulated to the issue of subjective theoretical argumentation (VASCONCELLOS, 1999 and to appear). In another words, it is extremely rare the find researches who do not adhere to the idea that speech (and language also) is mere behavior and the speaker, an epistemic subject. This dissertation assumes: (1) the autonomous functioning of language, as first proposed by Saussure (1916); developed in the european structuralism, by Jakobson and Benveniste and nowadays, revisited by authors like J-C Milner (1987, 2002) and De Lemos (1992, 2002) and (2) the hypotheses of the unconscious, as proposed by Freud and Lacan. This dissertation brings a reflection about the institutes of tong term stay, about the Cerebral Palsy person s institutionalization furthermore many discussions related to the subjective and clinics effects. The important knowledge about what is considered as disease, common (normal), not common (abnormal) and frailty, are also discussed. This theoretical perspective, assumed by the above mentioned authors is also sustained by investigators and clinicians who belong to the CNPq research group: Language acquisition, language pathology and language clinic , from LAEL-PUCSP, which is coordinated by Prof. Dr. Maria Francisca Lier-DeVitto and Prof. Dr Lúcia Arantes